2016
DOI: 10.1002/pssb.201600160
|View full text |Cite
|
Sign up to set email alerts
|

57Fe Mössbauer spectroscopy on iron based pnictides and chalcogenides in applied magnetic fields

Abstract: In this article, we show possibilities and limitations of the 57Fe‐Mössbauer spectroscopy applied to iron‐based pnictides and chalcogenides. The principle structure of these materials are FePn‐ or FeCh‐layers with tetragonally coordinated Fe2+ ions. These layers are the electronically active structures for the competing magnetic and superconducting ground states. Mössbauer spectroscopy is frequently applied to investigate zero field local magnetic properties of both powder and single crystal materials. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…However, it was shown that in the LaFeAsO-based compounds V zz is positive. 39,40 In the magnetic phase we obtained a pos-itive V zz value and thus we are confident that this is also the case in the paramagnetic phase of the CeFeAsO series.…”
Section: A Electric Field Gradientsupporting
confidence: 70%
“…However, it was shown that in the LaFeAsO-based compounds V zz is positive. 39,40 In the magnetic phase we obtained a pos-itive V zz value and thus we are confident that this is also the case in the paramagnetic phase of the CeFeAsO series.…”
Section: A Electric Field Gradientsupporting
confidence: 70%
“…The conversion ratio of Mössbauer hyperfine field and magnetic moment determined from neutron diffraction is −10 T/μ B . This is less than the typical value of iron arsenides/chalcogenides [40], approaching the value of −13 T/μ B for a predominant core contribution [67], which is typically observed in more localized systems. The localization-or reduced covalencycaused by the large Fe-Sb bond distance of 2.69Å [24] becomes apparent with regard to the Mössbauer isomer shift δ(T → 0) = 0.63 mm/s with respect to room temperature iron, which is 0.1 mm/s more than CuFeAs, amongst many other iron arsenides.…”
Section: Discussionmentioning
confidence: 60%
“…2 inset, Fig. 3) with a quadrupole splitting (Table II) typical for 122 compounds [40]. Below 11 K it broadens by ≈0.1 mm/s.…”
Section: B Zero Field (Zf) Mössbauer Spectroscopy Of Cufeasmentioning
confidence: 87%
See 1 more Smart Citation
“…The second component, Q2, has δ of 1.13 mm/s and ∆ΕQ of 1.80 mm/s, which are characteristic values for high-spin Fe 2+ . 45 This component has an intensity of 56% and a linewidth of 0.49 mm/s.…”
Section: Fe Mössbauer Spectroscopymentioning
confidence: 99%